2015
DOI: 10.5194/acp-15-951-2015
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric wet and dry deposition of trace elements at 10 sites in Northern China

Abstract: Abstract. Atmospheric deposition is considered to be a major process that removes pollutants from the atmosphere and an important source of nutrients and contaminants for ecosystems. Trace elements (TEs), especially toxic metals deposited on plants and into soil or water, can cause substantial damage to the environment and human health due to their transfer and accumulation in food chains. Despite public concerns, quantitative knowledge of metal deposition from the atmosphere to ecosystems remains scarce. To a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
94
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 234 publications
(103 citation statements)
references
References 84 publications
5
94
3
1
Order By: Relevance
“…gans, 2014; Pan et al, 2013). Due to rapid industrialization and urbanization in recent decades, China has become one of the most significant source regions for anthropogenic atmospheric emissions in the world (Guo et al, 2014).…”
mentioning
confidence: 99%
“…gans, 2014; Pan et al, 2013). Due to rapid industrialization and urbanization in recent decades, China has become one of the most significant source regions for anthropogenic atmospheric emissions in the world (Guo et al, 2014).…”
mentioning
confidence: 99%
“…However, the rate slowed down and was even negative in the 2000s, although the level of TMs in the atmosphere was still high. Pan et al found that AWD fluxes of TMs in North China were orders of magnitude higher than those in other regions, e.g., Hong Kong and the Yellow Sea in China, and the TM inputs to agricultural soils by atmospheric deposition were 10-78% of the anthropogenic input [4]. Recently, Xing et al reported that in Jiaozhou Bay, eastern China, the average contribution of AWD to surface water concentrations of TMs was between 1.1% and 12.3%, and heavy rain greatly increased TM concentrations in the surface water [18].…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric TM deposition is a key process in the biogeochemical cycles of these elements [3]. Their deposition rates are usually low in clean natural environments, which are infrequently affected by human activities, whereas rapid urbanization and industrialization have accelerated deposition rates in suburban and urban regions [4,5]. Atmospheric deposition is an essential source of TMs in terrestrial and aquatic ecosystems; however, excessive inputs lead to their accumulation, with potential harm to human health [6].…”
Section: Introductionmentioning
confidence: 99%
“…1). It has been recognized that anthropogenic emissions centered over this region (Kurokawa et al, 2013;Li et al, 2017), related atmospheric concentration, and depositions were severe in China (e.g., Pan et al, 2015). To overcome this limitation and advance our knowledge of precipitation chemistry over the whole of China, we added the following dataset for the chemical 10 concentration of precipitation over China.…”
Section: Nss-somentioning
confidence: 99%
“…The ground-based observation network in East Asia does not cover the northern China region, which is characterized by a large urban population and related anthropogenic emissions, and therefore atmospheric concentration and depositions were centered (e.g., Pan et al, 2015). The approach taken here will further promote our understanding of precipitation chemistry 15 for all of China.…”
Section: Introductionmentioning
confidence: 99%